East Africa Perspectives on the Book: Agricultural Extension - Global Status and Performance in Selected Countries - Davis, Kristin E.; Berhane, Guush; Mthinda, Catherine; Nkonya, Ephraim M. (2020)
Kristin Davis, Guush Berhane, Catherine Mthinda, Ephraim Nkonya WEBINAR East Africa Perspectives on the Book: Agricultural Extension – Global Status and Performance in Selected Countries OCT 28, 2020 - 03:30 PM TO 05:00 PM SAST